The Neuromodulatory Impact of Subthalamic Nucleus Deep Brain Stimulation on Gait and Postural Instability in Parkinson's Disease Patients: A Prospective Case Controlled Study - Szlufik, Stanislaw; Kloda, Maria; Friedman, Andrzej; Potrzebowska, Iwona; Gregier, Kacper; Mandat, Tomasz; Przybyszewski, Andrzej; Dutkiewicz, Justyna; Figura, Monika; Habela, Piotr; Koziorowski, Dariusz (Frontiers in Neurology, 2018)
Background: Subthalamic nucleus deep brain stimulation (STN-DBS) has been an established method in improvement of motor disabilities in Parkinson's disease (PD) patients. It has been also claimed to have an impact on balance and gait disorders in PD patients, but the previous results are conflicting. Objective: The aim of this prospective controlled study was to evaluate the impact of STN-DBS on balance disorders in PD patients in comparison with Best-Medical-Therapy (BMT) and Long-term-Post-Operative (POP) group. Methods: DBS-group consisted of 20 PD patients (8F, 12M) who underwent bilateral STN DBS. POP-group consisted of 14 post-DBS patients (6F, 8M) in median 30 months-time after surgery. Control group (BMT-group) consisted of 20 patients (11F, 9M) who did not undergo surgical intervention. UPDRS III scale and balance tests (Up And Go Test, Dual Task- Timed Up And Go Test, Tandem Walk Test) and posturography parameters were measured during 3 visits in 9 ± 2months periods (V1, V2, V3) 4 phases of treatment (BMT-ON/OFF, DBS-ON/OFF). Results: We have observed the slowdown of gait and postural instability progression in first 9 post-operative months followed by co-existent enhancement of balance disorders in next 9-months evaluation (p < 0.05) in balance tests (Up and Go, TWT) and in posturography examination parameters (p < 0.05). The effect was not observed neither in BMT-group nor POP-group (p > 0.05): these groups revealed constant progression of static and dynamic instability (p > 0.05). Conclusions: STN-DBS can have modulatory effect on static and dynamic instability in PD patients: it can temporarily improve balance disorders. mainly during first 9 post-operative months, but with possible following deterioration of the symptoms in next post-operative months.